Born this way : real stories of growing up gay - Vitagliano, Paul (Quirk Books, 2012)
Collected from around the world and dating from the 1940s to today, this collection of childhood photographs is accompanied by sweet, funny, and at time heartbreaking personal stories of growing up LGBTQ. The memories speak to the hardships of an unaccepting world and the triumph of pride, self-love, and self-acceptance.